Changes in Attitudes of Annelies in the Film “Bumi Manusia” by Hanung Bramantyo” - Bismil Tirta Jalisman (Universitas Pendidikan Indonesia, 2021)
Film as an art of moving images, intellectually, humans can see an event more real. Through film shows, each scene can be more easily read and understood because through the senses of the human eye it is directed to one scene perception. This study discusses changes in the attitude of the main character in the human world, namely Annalies. The problem discussed in this study is the change in the attitude of the main character in the film